Response of land cover to multi-scale spatial effects in complex karst mountainous areas - Qingqing Dai; Zhongfa Zhou; Denghong Huang; Yue Yang; Huanhuan Lu; Ya Li (Geocarto International)
The fragmented land surface and complex agricultural structures in karst mountainous areas lead to high heterogeneity of ground objects, intensifying the impact of spatial scale effects on land cover classification. This study reveals the influence of spatial scale effects on land cover classification in karst regions from the perspectives of landscape patterns and topographic complexity. The research indicates:(1) When the spatial resolution increases from 5m to 30m, the study area exhibits trends of reduced landscape fragmentation, concentrated land use distribution, and decreased landscape heterogeneity;(2) Scale effects vary among land cover types, with the variations in PD, LSI and AI for construction land exceeding those of the corresponding indices for other land cover types;(3) The decline rates of PD in low and high topographic complexity areas are 49.87% and 37.69% respectively, LSI decline rates are 31.88% and 8.81%, and AI decline rates are 23.70% and 11.32%.